IMPACT OF ORGANIZATIONAL CITIZENSHIP BEHAVIOUR ON MANAGERIAL EFFECTIVENESS OF MANAGERS IN PUBLIC AND PRIVATE SECTORS BANKS OF WEST BENGAL - Dr. Binay Krishna Halder (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
The aim of the present study is to identify the organizational citizenship behaviour as a predictor of managerial effectiveness of managers in both public and private sector banks of West Bengal. The sample consisted of 348 managers, out of which 174 were public and 174 were private banks managers. Stratified random sampling is used to collect the data. The standardized structured questionnaire named “Managerial Effectiveness Scale” was developed by Prof. S. Gupta (1996) and “Organizational Citizenship Behavior Check List” (OCB-C) was developed by Suzy Fox and Paul E. Spector (2009) was administered. Mean, SD, t- test, correlation and regression analysis were used to test the five hypotheses formulated in the study. The results indicated that there is no significant mean difference between the managerial effectiveness of managers of public and private sector banks. The results revealed a statistically significant positive correlation between organizational citizenship behavior and managerial effectiveness. The study concludes that organizational citizenship behaviour is a significant predictor of managerial effectiveness of managers.